ASSESSING THE CHALLENGES AND ISSUES OF IMPLEMENTING LIBRARY AUTOMATION IN LIBRARY: A STUDY - Kumar Jaiswal, Gaurav; Kumar Pandey, Praveen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
“This paper explores the concept of library automation, its evolution, benefits, challenges, and applications in modern libraries. It delves into the historical development of automated systems, examines current technological implementations, and discusses the issues faced during the transition from manual to automated processes. The study also highlights the impact of automation on library services and user experiences, Challenges, issue, implication and recommendations for effective implementation. The library automated is provide the as cataloging, circulation, and acquisitions to books, reducing manual workload of staff and minimizing errors. This efficiency allows staff to focus more on user engagement and service improvement. Library Automation ensures accurate record-keeping and facilitates the generation of detailed reports on various aspects of library operations. These insights support informed decision-making and strategic planning.”